Redistribution and Economic Growth in Integrated Economies - Günther Rehme (Technische Universität Darmstadt, Department of Law and Economics, 2004)
Many theoretical models show that redistribution causes low growth or capital outflows even though empirically redistribution and growth are often found to be positively associated across countries. This paper argues that tax competition and the danger of capital outflows leads optimizing governments to pursue high growth, no redistribution policies in technologically similar economies. However, the government of a technologically superior economy may attract foreign and domestically owned capital and may have relatively higher GDP growth and more resources for redistribution than in a closed economy. Thus, redistributing governments may have a relatively stronger interest in technological advance or high economic integration. The results imply that one may well observe a positive association between redistribution and growth across countries.
Keywords: C72; D33; F21; C21; O4; H21; 330; Growth; Redistribution; Tax Competition; Capital Mobility; Einkommensumverteilung; Wirtschaftswachstum; Steuerwettbewerb; Internationale Kapitalmobilität; Zwei-Länder-Modell; Innovationswettbewerb; Wirtschaftsintegration; Theorie